Foreign material ingestion in children and the role of endoscopy in symptomatic patients in South African hospitals - Sooka, Himal Navin (My University, 2019)
Background: Ingestion of foreign material by children is a common problem, and represents some of the most frequent presentations to paediatric casualty departments. The use of clinical signs and symptoms is challenging in determining which patients require urgent foreign body removal, as which patients may be treated conservatively. Objectives: To 1) describe the aetiology of foreign material ingestion in children, and 2) determine in which symptomatic patients endoscopy may be avoided. Methods: All children under 10 years who had ingested any foreign material between November 2013 and November 2015 were recruited into the study. Patients were classified as symptomatic or asymptomatic. Symptomatic patients were further sub-classified as mild, moderate, or severe based on clinical signs. All symptomatic patients underwent urgent endoscopy. Asymptomatic patients with foreign bodies lodged in the oesophagus were admitted for semi-urgent removal by endoscopy. Results: A total of 138 paediatric patients were included in the study. There were a total of 105 solid objects (76%), and 32 fluid material ingested (23%). There was a significant association between symptomatic status and class of material ingested (p = 0.001). Endoscopy rate was significantly higher for patients who had ingested foreign objects (85.6%) compared to those who had ingested corrosive materials (36.4%) (p < 0.0001). Conclusion: Endoscopy is mandatory in all symptomatic patients with a history of foreign material, and should be undertaken as soon as possible. No definitive conclusions may be drawn to affect current clinical practice due to the limitation of a small sample size.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine Johannesburg 2019